Learning a Practical Psychotherapeutic Skill in Higher Education in Sweden: A Conceptual Paper Concerning the Importance of Constructive Alignment When Teaching Therapeutic Alliance - Ann-Sophie Lindqvist Bagge; Rolf Holmqvist; Therése Skoog; Malin Hildebrand Karlén (Clinical Psychology in Europe)
[Background] In addition to theoretical education, clinical psychology programs should include practical skills training. This skill training may be tied to specific assessment and treatment methods; other skills, such as the ability to create a collaborative alliance with patients, are more generic. Previous research has shown that the ability to build a therapeutic alliance (TA) is often not systematically taught in clinical psychology programs and it is uncertain how this competence is examined. A lack of competence in establishing TA on the part of the psychologist might diminish the effects of psychotherapy. To meet the Bologna Declaration, European universities need to demonstrate constructive alignment, i.e. a relationship between elements of the course content and intended learning outcomes in course documents, and show how the acquired knowledge, abilities, and approaches are assessed. [Method] This conceptual paper reviewed the syllabuses for universities in Sweden offering the five-year clinical psychology program to illustrate how higher education in Sweden adheres to the Bologna recommendation on constructive alignment when teaching TA to future clinical psychologists. [Results] Only two universities out of all eleven universities in Sweden offering a psychology program described satisfactory constructive alignment concerning TA. [Conclusion] This conceptual paper raises awareness of the importance of pedagogic structure when teaching TA in higher education by pointing to the prevailing lack of constructive alignment in teaching TA. The increased awareness will hopefully lead to improved structuring in the teaching of TA.